IDENTIFIKASI GAMBAR CADAS PADA CERUK MAKAMPILO DI DESA LIANGKABORI KECAMATAN LOHIA KABUPATEN MUNA - Nengsi Rahmawati; Abdul Alim; Ainussalbi Al Ikhsan (SANGIA: Jurnal Penelitian Arkeologi, 2024)
The Makampilo Ceruk site is one of the niches that has rock art. The site is in Liangkabori Village, Lohia District, Muna Regency, Southeast Sulawesi Province. This site has never had any research discussing rock art. So the author is interested in taking the title on the site.This research aims to find out and identify image motifs and variations in the form of rock images at the Ceruk Makampilo Site. Then, the method used in this research is data collection, data recording and data processing using ImagJ software to make the images clearer.Based on the results of research conducted, the Ceruk Makampilo Site has 18 panels with the number of images found being 18 images. The found images have different motifs. These motifs include human motifs with a total of 4 variants, ani mal motifs with a total of 7 variants, geometric motifs with a total of 3 variants and abstract motifs with a total of 47 images. Meanwhile, the shape of the image on the Ceruk Makampilo Site.